Sustainability and Climate Change Will Become Game Changers – Shortly - Novak, David (Archives of Business Research, 2022)
Purpose: Status regarding climate change and needed activities - The 2015 Paris Agreement was the first global climate conference to set binding targets that must be implemented. Climate change must be combated globally, based on the UN guidelines on the sustainability triangle and the 17 goals. The necessary changes in technologies will affect everyone, regardless of whether they are business (in- cluding SMEs there), society / politics and climate protection / sustainability. In the energy sector (production, distribution and application) in particular, massive changes will have to be made as part of the imperative to decarbonize. Design / methodology / approach: The goal was to write a short report on the status quo in the area of sustainability and anthropogenic climate change and also to add a vision of how it could look like to- day and possibly at the end of the 21st century based on the current state of knowledge. Findings: Climate protection and sustainability will increasingly have to be implemented and lived, which is particularly challenging for young people. The energy sector will therefore have to go through the greatest transformation in a necessarily short time that has ever happened. The energy strategies of the future, based on decarbonization, will have to realign themselves with new energy sources such as hydrogen H2 and their new generation countries with sun and wind. Affected countries: Numerous countries, which are offered these geographical opportunities, become winners in the new competition for income from energy generation, largely paid for by industrialized countries that lack enough free space for wind and solar energy. Emerging and developing countries that are still poor today are opening up unimagined opportunities for high income from hard curren- cies. Research / Future / Practical Implications: Visions based on the coming energy transition can be derived from this. It will be by far the largest investment in an industry in a short period of time that can probably only be paid for and controlled by the World Bank and the central banks. It will be a gi- gantic and expensive challenge for everyone involved (state, economy, population). Not to do so would become even more expensive in the long term, not to mention the catastrophic effects, specifi- cally also on humanity. So if we don’t have a choice - let’s go for it! Originality / value: There is currently very little scientific and even less empirical literature on this entire area. Nevertheless, or precisely because of the massive time pressure imposed by politics and for humanity worldwide, it has to be written and reported on scientifically.